HISTÓRIA E CONTEXTO DA GUERRA SIRO-PALESTINENSE (SIRO-EFRAIMITA): UMA ANÁLISE EXEGÉTICA DE ISAÍAS 7.1-9 - VICENTE, THIAGO GUIMARÃES (2020)
This is an investigation into the present state of the book of Isaiah, the exegesis of Isaiah 7:1-9, and the historical context of the war called siro-efraimite. We understand that this is a book unified and expanded through a literary composition over the centuries, and no longer seen in its tripartite form, as much as its composition and vision. His research guided us to continue with our exegesis, considering the book, in its final, canonical aspect. The text of Is 7.1-9 is known to demonstrate a coalition between Syria and Israel against Judah to exchange King Ahaz, a fact that is called the Syro-Ephraimite war. In the exegesis of the text, we perceive a clearly Judaic wording, which values the Davidic dynasty with a Deuteronomic reinterpretation of salvation, where believing in YHWH is sufficient for salvation. It also demonstrates a possible justification for Judah's exile, as they did not believe and did not remain, and also a return from exile in the name of the son of the prophet Isaiah, who accompanies him to carry YHWH's message to King Ahaz: Sear-Jasube (One-rest-will return). When we searched in other biblical texts about the war called Syro-Ephraimite, in the Assyrian collection of Tiglate-Pileser III, we realized that, in fact, it is a Syrian-Palestinian war. An anti-Assyrian alliance against the powerful Neo-Assyrian empire of Tiglate-Pileser III, consisting of the states of Syria, Israel, Tire, Gaza, Asquelom, Arabs, Edom and Egypt. And for that reason, Tiglate-Pileser III reportedly waged a military campaign against the region, from 734 to 732 aEC, which culminated in the fall of Syria and northern Israel, which were annexed to Assyria, and in subjugation, all were also other states in the region.